Disaster Mental Health Epidemiology: Methodological Review and Interpretation of Research Findings. Issue 2 (2nd April 2016) - North, Carol S.
Abstract : Worldwide, disasters are increasing in frequency and severity. Mental health consequences of disasters are extensive, and knowledge of anticipated mental health effects is needed for effective disaster response. Difficulties inherent in conducting disaster research have limited the understanding of research findings. This article presents and interprets disaster mental health research findings in the context of research methods. A brief history of the disaster mental health research field is provided, and the presentation of findings is ordered into topical areas of disaster mental health consequences and timing and prediction of mental health outcomes. Results of different studies varied greatly by several main characteristics of research methods, especially methods of psychiatric assessment, sampling and exposure group determination, and consideration of confounding variables. In conclusion, many complexities in conducting disaster mental health research have limited the understanding and interpretation of available knowledge needed to inform efforts to plan and carry out effective mental health responses to disasters. Thoughtful interpretation of findings in the context of research design and methods is vital to accurate understanding of the types, prevalence, and predictors of anticipated mental health effects of disasters. A wealth of knowledge from disaster mental health research has accumulated in recent decades, but more research is still needed to resolve inconsistent findings through methodological refinements.